Nickel-cobalt bimetallic anode catalysts for direct urea fuel cell - Xu, Wei; Zhang, Huimin; Li, Gang; Wu, Zucheng (Scientific reports, 2014)
Nickel is an ideal non-noble metal anode catalyst for direct urea fuel cell (DUFC) due to its high activity. However, there exists a large overpotential toward urea electrooxidation. Herein, NiCo/C bimetallic nanoparticles were prepared with various Co contents (0, 10, 20, 30 and 40 wt%) to improve the activity. The best Co ratio was 10% in the aspect of cell performance, with a maximum power density of 1.57 mW cm −2 when 0.33 M urea was used as fuel, O 2 as oxidant at 60°C. The effects of temperature and urea concentration on DUFC performance were investigated. Besides, direct urine fuel cell reaches a maximum power density of 0.19 mW cm −2 with an open circuit voltage of 0.38 V at 60°C.